The future of journalistic work: its changing nature and implications - Rottwilm, P (Reuters Institute for the Study of Journalism, 2014)
Changes in the structural arrangements of journalistic labour and the nature of journalistic work have profound implications for the future of professional journalism. This report lays out the issues and challenges that the evolving nature of journalism present to working journalists and their roles.